Characterization of Sarcoptes scabiei cofilin gene and assessment of recombinant cofilin protein as an antigen in indirect-ELISA for diagnosis. Issue 1 (December 2015) - Zheng, Yu; He, Ran; He, Manli; Gu, Xiaobin; Wang, Tao; Lai, Weimin; Peng, Xuerong; Yang, Guangyou
Abstract Background Scabies impairs the health of humans and animals and causes heavy economic losses. Traditional diagnostic methods for scabies are inefficient and ineffective, and so far there is no commercial immunodiagnostic or molecular based test for scabies. Methods Here, we used recombinantSarcoptes scabiei cofilin protein as an antigen to establish indirect ELISA.S. scabiei cofilin is highly homologous toDermatophagoides farinae Der f 31 allergen (90 % identity). TheS. scabiei cofilin gene was cloned and expressed inEscherichia coli to obtain recombinant protein. Western blotting and fluorescence immunohistochemistry were carried out, and we established an indirect ELISA method and detected 33 serum samples from scabies infected rabbits and 30 serum samples from naïve rabbits. Results Western blotting demonstrated thatS. scabiei cofilin possessed good immunogenicity and fluorescence immunohistochemistry showed theS. scabiei cofilin is widespread in the splanchnic area of mites. In ELISA, a cut-off value of 0.188 was determined to judge experimental positive and negative serum values. Specificity and sensitivity of the ELISA were 87.9 and 83.33 %, respectively. Conclusions RecombinantS. scabiei cofilin showed potential value as a diagnostic antigen. The ELISA method established could be used in clinical diagnosis and provide experimental information in minimal or asymptomatic infection.